The Ibadan glaucoma study (2003)
To obtain epidemiological data on the prevalence and risk factors for open angle glaucoma in hospital workers of African origin, and investigate appropriate methods of a rapid, cost-effective screening procedure for glaucoma. A cross-sectional study of workers in the University College Hospital (UCH) Ibadan, using a structured questionnaire for data collection. The variables available for data analysis include workers demographic characteristics, visual acuity, pupil status, intraocular pressure, cup-disc ratio, central visual fields, family history of glaucoma, chronic diseases such as hypertension and diabetes. The data was analysed with EPI-INFO version 6.02 for simple analysis, while the SPSS package was used for multivariate analysis. A total of two thousand, one hundred and nine (2, 109) UCH workers participated in the screening exercise for glaucoma. A high majority of the workers 1794 (85.1 %) were negative to the diagnosis of glaucoma, while the remaining 315 (14.9%) were suspected to have glaucoma out of which 57 (2.7%) were confirmed as definite glaucoma cases. The prevalence of glaucoma among UCH workers was 27 per 1000, 95%, confidence interval = 20 per 1000,35 per 1000. Factors associated with glaucoma were relative afferent pupillary defect, cup-disc ratio greater than 0.7, intraocular pressure, family history of glaucoma and the presence of chronic diseases such as diabetes. The left eye appears to have a higher probability of ocular problems compared with the right eye. The prevalence of glaucoma among hospital workers was 2.7% The cup-disc ratio appears to be a better diagnostic tool for glaucoma since it gives the best positive predictive value (with a cut-off point of 0.7) than all other variables.